Killing Vector Fields in Generalized Conformal β-Change of Finsler Spaces - Mallikarjun Yallappa Kumbar; Narasimhamurthy Senajji Kampalappa; Thippeswamy Komalobiah Rajanna; Kavyashree Ambale Rajegowda (Journal of Mathematics)
We consider a Finsler space equipped with a Generalized Conformal β-change of metric and study the Killing vector fields that correspond between the original Finsler space and the Finsler space equipped with Generalized Conformal β-change of metric. We obtain necessary and sufficient condition for a vector field Killing in the original Finsler space to be Killing in the Finsler space equipped with Generalized Conformal β-change of metric.